Comparison of influenza vaccination coverage between immigrant and Australian-born adults. Issue 50 (7th December 2016) - Karki, Surendra; Dyda, Amalie; Newall, Anthony; Heywood, Anita; MacIntyre, C. Raina; McIntyre, Peter; Banks, Emily; Liu, Bette
Highlights: We estimated influenza vaccination coverage in older adults in Australia. The coverage was lower in immigrants and varied by country of birth. Coverage did not differ by age at migration and years lived in Australia. Vaccination programs should consider the needs of immigrants. Abstract: Australia has a large immigrant population but there are few data regarding whether influenza vaccine coverage in adults varies according to country of birth. We quantified and compared self-reported influenza vaccination coverage between Australian-born and immigrant residents aged ⩾49 years enrolled in a large cohort (the 45 and Up Study), surveyed in 2012 and 2013. Estimated vaccine coverage was adjusted for age, sex and other factors known to be associated with vaccine uptake. Among 76, 040 participants included in the analyses (mean age 66.2 years), 21.6% were immigrants. In Australian-born adults aged 49–64 and 65+ years the age- and sex-adjusted estimates for influenza vaccination within the year prior to survey was 39.5% (95% CI 38.9–40.0) and 70.9% (70.4–71.5) respectively. The corresponding estimates in immigrants were significantly lower at 34.8% (33.7–35.8) and 64.4% (63.4–65.4) respectively. Among immigrants, coverage varied by region of birth, and was slightly lower among those who spoke a language other than English at home compared to those who only spoke English. Among immigrants there was no significant difference in coverage comparing those who migrated when they were children to those who migrated as adults and coverage did not differ significantly according to years lived in Australia. Programs to increase adult vaccination coverage should consider the needs of immigrants.